2010
DOI: 10.1098/rspb.2010.1697
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy model for antibody-mediated pre-erythrocytic malaria vaccines

Abstract: Antibodies to the pre-erythrocytic antigens, circumsporozoite protein (CSP), thrombospondin-related adhesive protein (TRAP) and liver-stage antigen 1, have been measured in field studies of semiimmune adults and shown to correlate with protection from Plasmodium falciparum infection. A mathematical model is formulated to estimate the probability of sporozoite infection as a function of antibody titres to multiple pre-erythrocytic antigens. The variation in antibody titres from field data was used to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Protective immunity against malaria associates with circulating IgG Abs against CS (47). Previous studies have also shown the ability of fusion proteins to induce strong humoral responses based on their ability to form large molecular mass aggregates (20).…”
Section: Discussionmentioning
confidence: 99%
“…Protective immunity against malaria associates with circulating IgG Abs against CS (47). Previous studies have also shown the ability of fusion proteins to induce strong humoral responses based on their ability to form large molecular mass aggregates (20).…”
Section: Discussionmentioning
confidence: 99%
“…We used the model-predicted anti-CSP antibody titres over time to estimate a dose–response curve for the relationship between antibody levels and protection from infection and disease using survival analysis methods [[21],[22]]. Vaccine efficacy against infection V ( t ) is estimated from antibody titre CSP ( t ) according to the following dose–response curve:Vitalict=italicVmax111+)(italicCSP)(tβitalicαwhere α and β are shape parameters to be estimated, and V max is the maximum efficacy against infection [[21]].…”
Section: Methodsmentioning
confidence: 99%
“…TRAP has been reported to be a target for T cell-based vaccines, but some studies have also shown the importance of antibodies against TRAP as protective effector molecules against malaria [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%